Endothelial function provides early prognostic information in patients with COVID-19: a cohort study - Oliveira, Murilo Rezende (2021)
Background: The prothrombotic phenotype and diffuse intravascular coagulation observed in COVID-19 reflect endothelial dysfunction, which is linked to blood flow delivery deficiencies and cardiovascular risk. Assessments of detect vascular deficiencies among newly diagnosed and hospitalized patients due to COVID-19 have yet to be determined. Objective: To assess endothelial function characteristics in relation to length of hospitalization and mortality in patients diagnosed with COVID-19 and compare to patients without COVID-19. Methods: A prospective observational study involving 180 patients with confirmed COVID-19 (COVID-19 group) or suspected and ruled out COVID-19 (Non-COVID-19 group). Clinical evaluation and flow mediated vasodilation (FMD) were performed between the first 24-48 h of hospitalization. Patients were followed until death or discharge. Results: We evaluated 98 patients (COVID-19 group) and 82 (Non-COVID-19 group), COVID-19 group remained hospitalized longer and more deaths occurred compared to the Non-COVID-19 group (p = 0.01; and p < 0.01). Patients in COVID-19 group also had a significantly greater reduction in both FMDmm and FMD% (p < 0.01 in both). We found that absolute FMD≤0.26 mm and relative FMD≤3.43% were the ideal cutoff point to predict mortality and longer hospital stay. In Kaplan Meyer's analysis patients had a high probability of death within a period of up to 10 days of hospitalization. Conclusion: Patients hospitalized for COVID-19 present endothelial vascular dysfunction early, remained hospitalized longer and had a higher number of deaths, when compared with patients without COVID-19.